2022
DOI: 10.3390/jox12030015
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine-Disrupting Effects of Bisphenol A on the Cardiovascular System: A Review

Abstract: Currently, the plastic monomer and plasticizer bisphenol A (BPA) is one of the most widely used chemicals. BPA is present in polycarbonate plastics and epoxy resins, commonly used in food storage and industrial or medical products. However, the use of this synthetic compound is a growing concern, as BPA is an endocrine-disrupting compound and can bind mainly to estrogen receptors, interfering with different functions at the cardiovascular level. Several studies have investigated the disruptive effects of BPA; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 136 publications
0
29
0
Order By: Relevance
“…Fonseca et al 8 also confirmed the effect of BPA on increase the risk of cardiovascular diseases and recommended storing food in glass containers and reducing plastic containers in order to improve lifestyle and decrease exposure to BPA. In addition, plastic bottles have a weaker structure than glass and are more difficult to clean.…”
Section: Implications To Safety Of Baby Bottlesmentioning
confidence: 91%
See 1 more Smart Citation
“…Fonseca et al 8 also confirmed the effect of BPA on increase the risk of cardiovascular diseases and recommended storing food in glass containers and reducing plastic containers in order to improve lifestyle and decrease exposure to BPA. In addition, plastic bottles have a weaker structure than glass and are more difficult to clean.…”
Section: Implications To Safety Of Baby Bottlesmentioning
confidence: 91%
“…Hormonal and reproductive disorders, breast and prostate cancers, delayed maturation in women, and infertility in men have also been reported which resulted from exposure to BPA. 6 , 7 For example in the study of Fonseca et al, 8 the increased risk of adult cardiovascular diseases and gestational hypertension disorders by exposure to BPA caused through intracellular processes, inhibition of main ion routs, changes in Ca 2+ movement, induction of oxidative stress, and epigenetic changes.…”
Section: Introductionmentioning
confidence: 99%
“…One of the primary monomers studied by the scientific community, due to its environmental ubiquity and high level of detection in human biological fluids, is bisphenol A (BPA). Due to its high production volume and multiplicity of uses, BPA is considered one of the most widely used monomers in the world [8]. Thanks to its chemical properties [9], it can move throughout the human body and cross biological barriers, so it is commonly found in urine, blood, breast milk, and even amniotic fluid [7,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Its structure is stable and can exist in the environment for a long time, posing a great threat to human health. Fonseca et al 1 found that long‐term exposure to BPA increases the risk of cardiovascular disease and hypertensive disorders of pregnancy in adults. Yazdani et al 2 found that prolonged exposure of salmon to BPA resulted in oxidative lesions in kidney cells and caused transcriptional responses of immune genes.…”
Section: Introductionmentioning
confidence: 99%